2014
DOI: 10.1017/s026646741400011x
|View full text |Cite
|
Sign up to set email alerts
|

Context dependency of rewards and services in an Indian ant–plant interaction: southern sites favour the mutualism between plants and ants

Abstract: Borges (2014). Context dependency of rewards and services in an Indian ant-plant interaction: southern sites favour the mutualism between plants and ants .Abstract: Protection-based ant-plant mutualisms may vary in strength due to differences in ant rewards, abundance of protective ants and herbivory pressure. We investigated geographical and temporal variation in host plant traits and herbivory pressure at five sites spanning the distribution range of the myrmecophyte Humboldtia brunonis (Fabaceae) in the Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The morphs (δ, ε) with simple, tube-like buccal cavities devoid of effective armature seem to compete for a temporary bacterial food source whereas the predatory morphs (α, γ) emerge next coinciding with the proliferation of wasp-transmitted nematodes in the syconium. Development of greater number of morphs might be due to the high climatic and seasonal variation which is observed in southern India (Gadgil & Joshi, 1983;Gunnel 1997;Peel et al, 2007;Shenoy & Borges, 2010;Chanam et al, 2014). We observed sex specific stomatal morphs (β = adult female only) versus (γ,δ, ε = adult males only) which requires further validation through a study similar to that reported in Susoy et al (2016) with Pristionchus sycomori where different early and late interfloral (phase C) figs were examined and large numbers of Pristionchus were sexed and assessed for stomatal morphotype.…”
Section: Discussionmentioning
confidence: 99%
“…The morphs (δ, ε) with simple, tube-like buccal cavities devoid of effective armature seem to compete for a temporary bacterial food source whereas the predatory morphs (α, γ) emerge next coinciding with the proliferation of wasp-transmitted nematodes in the syconium. Development of greater number of morphs might be due to the high climatic and seasonal variation which is observed in southern India (Gadgil & Joshi, 1983;Gunnel 1997;Peel et al, 2007;Shenoy & Borges, 2010;Chanam et al, 2014). We observed sex specific stomatal morphs (β = adult female only) versus (γ,δ, ε = adult males only) which requires further validation through a study similar to that reported in Susoy et al (2016) with Pristionchus sycomori where different early and late interfloral (phase C) figs were examined and large numbers of Pristionchus were sexed and assessed for stomatal morphotype.…”
Section: Discussionmentioning
confidence: 99%
“…, Chanam et al . ). Domatia‐bearing plants are rewarded by nitrogen absorbed from domatia that are occupied even by non‐protective EFN‐consuming ants (Chanam et al .…”
Section: Relative Percent Compositions and Concentrations Of Sugars Amentioning
confidence: 97%
“…, Chanam et al . ) and within the context of a trophic mutualism with ants (Chanam et al . ) but also to distract the ants from tending Hemiptera.…”
Section: Relative Percent Compositions and Concentrations Of Sugars Amentioning
confidence: 99%
“…Humboldtia brunonis is one of the rare ant-plant species in which both domatia-bearing and domatia-free individuals occur 14 . In this species, the proportion of domatia-bearing plants varies geographically and is higher in sites with stronger herbivore pressure 15 . Ants that live on plants sometimes cut floral buds, which increases vegetative growth, and eventually benefits the ant colony.…”
Section: Introductionmentioning
confidence: 96%